Real-world evidence study on the early use of cemiplimab in the UK: REACT-CEMI (Real World evidence of advanced CSCC treatment with cemiplimab) - Challapalli, Amarnath; Stewart, Grant; Shaw, Heather; Davies, Peter John; Lopez-Baez, Juan Carlos; Ottley, Edward C.; Kelly, Stephen (Frontiers in Immunology, 2024)
Background: Cemiplimab was licensed in the United Kingdom (UK) in 2019 for the treatment of patients with locally advanced and metastatic CSCC not suitable for curative surgery or radiotherapy (advanced CSCC [aCSCC]). No UK multi-center studies have investigated the real-world experience of cemiplimab post marketing authorisation in aCSCC. Methods: This non-interventional retrospective study (10 UK centers) involved data collection from medical records of patients with aCSCC who initiated cemiplimab treatment between 2 July 2019 and 30 November 2020. The study period was a minimum of 12 and a maximum of 36 months post cemiplimab initiation. The primary objective was to describe the real-world clinical effectiveness of cemiplimab (primary outcome: overall response rate [ORR]). Results: Of 105 patients, 70% (n=73/105) were male (median [range] age at index of 78.5 [55.4–93.2] years); most patients (63% [n=50/80]) had an Eastern Cooperative Oncology Group (ECOG) score of 1 and 62% (n=63/102) had metastatic disease. The ORR within 12 months was 42% (95% confidence interval [CI] 32%–51%) and the disease control rate was 62% (n=65/105). The median (95% CI) real-world progression-free survival and overall survival from index was 8.6 (6.0–18.7) and 21.0 (14.7–25.2) months, respectively. The median (range) number of cemiplimab infusions was 11.0 (1.0–44.0). Eighty-seven percent experienced no cemiplimab treatment interruptions; 13% (n=14/105) interrupted treatment due to immune-related adverse reactions (irARs) (47% [n=9/19] of treatment interruption events). Eighty-five percent (n=89/105) of patients had discontinued cemiplimab treatment by the end of the study; where reasons for discontinuation were recorded, 20% (n=17/87) discontinued due to the completion of their 2-year treatment course. Nineteen percent (n=20/105) of patients experienced irARs. Conclusion: Effectiveness and safety data in this study are broadly similar to previous real-world studies of cemiplimab and the EMPOWER-CSCC1 clinical trial; with our cohort representing a broader population (included immunocompromized and transplant patients). Results support the use of cemiplimab for the treatment of aCSCC in a real-world setting.